Epidemiological situation of TB – HIV co-infection in Baixada Santista between 2006 and 2016 (Research, Society and Development, 2022)
To perform an analysis of HIV as a risk factor for the outcome of death in patients co-infected with Tuberculosis in the city of Santos – SP between 2006 and 2016. Study with a retrospective design comprising 18850 cases of Tuberculosis reported in Baixada Santista between 2006 and 2016. To perform an analysis of HIV as a risk factor for the outcome of death in patients co-infected with Tuberculosis in the city of Santos – SP between 2006 and 2016. The database was obtained from the Center for Epidemiological Surveillance of the State of São Paulo (CVE -SP). During the study period, 1984 cases of TB/HIV co-infection were reported, representing 12.8% of the total sample (15488). Of the co-infection cases, 35.3% were female and 64.7% male, and the gender variable did not show a statistically significant association with the HIV variable (p=0.097). We had a predominance of HIV/TB co-infection cases in patients aged between 30 – 50 years, these account for 65.9% of patients with co-infection. we observed that 17.4% of patients abandoned treatment before completion and that the cure rate was 55.6% for this population; The outcome and HIV variables showed a statistically significant association (p < 0.001). We conclude that there was no statistically significant association between TB/HIV co-infection and gender. The variables age, treatment dropout and cure were statistically significant when evaluated using statistical tests. The mortality rate, as well as the treatment dropout rate were proportionally higher in those patients co-infected with TB/HIV when compared to patients infected only with Tuberculosis.